Evaluation of the anti-Leishmania mechanisms of Annona glabra L. (Annonaceae): A brief review (Research, Society and Development, 2021)
Leishmaniasis is a neglected tropical disease caused by protozoan parasites of the genus Leishmania and characterized by the formation of skin ulcers. Despite the large number of cases, reaching worldwide proportions, there are many factors to be discussed regarding the treatment of the disease, which although much discussed, is still poorly elucidated. The objective of this review study is to identify the main anti-Leishmania mechanisms of Annona glabra L. (Annonaceae). This is a literature review study. To this end, we used the following descriptors in the search: natural products, leishmaniasis, mechanism of action and Leishmania (together and separately). In the selection criteria we opted for full articles, in the period 2012 - 2021 (last 10 years), in Portuguese and English. The searches were performed in the following databases: Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and Google Scholar. The articles were selected first by title, then by abstract, and finally by complete reading. The potential of natural products and their use in traditional medicine for the treatment of diseases makes them the target of research for new drugs. Different Annona species have demonstrated antileishmanial activity when evaluated in vitro. The substances that show leishmanicidal activity in Annona glabra extract are the alkaloids. New studies can be developed to elucidate even more specifically the effects of this natural product in vivo, in an attempt to obtain a new pharmacological alternative for the treatment of leishmaniasis.